Seismic Structural Interpretation Study of Mishrif Formation in Nasiriyah Oil Field Southwestern Iraq - Z. Khorshid, Salman; A. Hlelai, Mahmoud (Iraqi Journal of Science, 2023)
Seismic data interpretation study has been done for Mishrif Formation in Nasiriyah oil field at the southern part of Iraq in order to update the structural image of Mishrif reservoir which is currently the main unit bearing the oil in subsurface area covered about (447) km2. This study is achieved by using Petrel, IP, and other approval software. Seismic to well tie method in conventional qualitative interpretation used to re-identify the top and bottom of the Mishrif reservoir which converted into structural depth maps and then followed by constructing and developing 3-D structural model helped to understand the vertical and lateral thickness extensions heterogeneity of Mishrif Formation in the field. The cap rock (CRI) has thickness ranging from (4 - 14) m, it increases in (NW) and (SE), and decreases in the middle of the field. (MA) unit has thickness ranging from (53 -63) m, and it increases in (N) and decreases in the (S) of the field. The cap rock (CRII) unit has almost the same thickness in the entire field. It was ranging between (10- 12) m. (MB1) unit has thickness ranging from (11 -23) m and it was increases in (W) and decreases in the (E) of the field. (MB2) has thickness ranging from (35 -55) m increases to the (E) and almost has same thickness in the entire field. Its showed that Mishrif reservoir could be a marine platform formed gradually from back reef in NW to the reef slope in SE of the field.